(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The article studies the effect of inoculation of chickpea seeds with root rot bacteria on field germination and plant survival. According to the results of the experiment, in the variants treated with biological preparations, field germination of seeds increased by 6–12%, and plant survival by 8–15%. In the inoculated variants, the root system of plants was well developed and the number of roots increased. The results obtained indicate the effectiveness of using biological methods in chickpea cultivation.